2008
DOI: 10.1093/aob/mcn200
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and genetic diversity of the dense-flowered orchid, Neotinea maculata, at the centre and edge of its range

Abstract: Background and Aims Species may occur over a wide geographical range within which populations can display large variation in reproductive success and genetic diversity. Neotinea maculata is a rare orchid of conservation concern at the edge of its range in Ireland, where it occurs in small populations. However, it is relatively common throughout the Mediterranean region. Here, factors that affect rarity of N. maculata in Ireland are investigated by comparing Irish populations with those found in Italy, where it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 67 publications
0
32
2
1
Order By: Relevance
“…Many studies in orchids have reported a lower level of population differentiation than reported in the present study (e.g. [16] [24] [58] [64]. Most of them identified high gene flow between populations through pollen, and/or seed dispersal as the potential causes.…”
Section: Genetic Diversity and Population Structurecontrasting
confidence: 47%
“…Many studies in orchids have reported a lower level of population differentiation than reported in the present study (e.g. [16] [24] [58] [64]. Most of them identified high gene flow between populations through pollen, and/or seed dispersal as the potential causes.…”
Section: Genetic Diversity and Population Structurecontrasting
confidence: 47%
“…Numerous subsequent studies have also found low genetic differentiation among orchid populations (for example, Chung et al, 2005;Esfeld et al, 2008;Swarts et al, 2009). Self-fertilization may contribute to the high differentiation of I. medeoloides populations (Hamrick and Godt, 1996), although Neotina maculata, another selfing orchid species, has low population differentiation (Duffy et al, 2009). The tiny and widely separated populations of I. medeoloides may also contribute to its strong genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…They found that maximum total phenolic content was 53.1 mg GAE/g dry weight by using 5% HCl and this value decreased by using boiling water (38.4) followed by 50% ethanol (25.9), while using cold water the total phenolic content was 15.1 mg GAE/g dry weight. These differences of phenolic content might be due to numerous factors, including types of extraction, kind of solvents ,climatic variables, growing environment, plant age and harvesting time as well as the origin of the sample (Douglas et al, 2004& Duffy et al, 2009). …”
Section: Total Phenolic Contentsmentioning
confidence: 99%